2021
DOI: 10.1155/2021/4919391
|View full text |Cite
|
Sign up to set email alerts
|

Malyngamide F Possesses Anti-Inflammatory and Antinociceptive Activity in Rat Models of Inflammation

Abstract: Objective. Inflammation and pain are involved in the pathophysiology of various clinical conditions. This investigation aims to probe the analgesic and anti-inflammatory activity of Maltoamide F. Methods. The possible toxicity of Maltoamide F was evaluated by an acute toxicity test. To assess the anti-inflammatory and antinociceptive effects of Maltoamide F on rats, the models of carrageenan-caused paw edema, xylene-induced ear edema, arachidonic-acid- (AA-) induced ear edema, formalin-caused plantar edema, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has also been demonstrated that the mega molecular polysaccharide sacran extracted from cyanobacterium Aphanothece sacrum has topical anti-inflammatory effects at concentrations of 0.01 and 0.05% (w/v) in the ultimate product ( 24 ). Moreover, Malyngamide F, a lipo-peptide of a filamentous cyanobacterium Lyngbya majuscule , showed anti-inflammatory and anti-nociceptive effects in animal models through reducing the levels of inflammatory cytokines, PGE-2, IL-6, and TNF-α ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the mega molecular polysaccharide sacran extracted from cyanobacterium Aphanothece sacrum has topical anti-inflammatory effects at concentrations of 0.01 and 0.05% (w/v) in the ultimate product ( 24 ). Moreover, Malyngamide F, a lipo-peptide of a filamentous cyanobacterium Lyngbya majuscule , showed anti-inflammatory and anti-nociceptive effects in animal models through reducing the levels of inflammatory cytokines, PGE-2, IL-6, and TNF-α ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ZINC06804365 has been tested and reported as a potential inhibit for many signaling pathways such as Wnt-3a and also as having inhibitory activity against the Tankyrase-2 enzyme which reportedly has anti-cancer activities [ 74 ]. Malyngamide V has been widely studied for its anti-inflammatory and antinociceptive role [ 75 ] and CMNPD3609 possesses several antibacterial activities [ 76 ]. The diverse role of these compounds in different cancer and antimicrobial activities makes them a possible drug candidate to curb CRC caused by F. nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…In the early phase (0–3 h after injection), the inflammatory response is mediated by the release of inflammatory mediators such as histamine, 5-HT, and serotonin, whereas the late phase (3–5 h after injection) is mediated by the release of bradykinin, TNF-α, and leukotrienes and is sustained by increased levels of COX-2 and PGE 2 . Commercially available anti-inflammatory drugs target the late phase [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%